Why it’s not all about the learner: A sociomaterial account of students’ digital literacy practices - Gourlay, Lesley; Oliver, Martin (Proceedings of the International Conference on Networked Learning, 2014)
Digital literacies are seen as an important area of current research and practice, but most accounts of this rely on capability or competence models of "digital literacy". These decontextualised, cognitive accounts ignore the insights of New Literacy Studies (e.g. Lea & Street, 1998), which have shown that focusing on a ’free floating’ learner, ignoring settings, resources and cultures, and failing to explain important aspects of how literate practice is achieved and enacted. Adopting a sociomaterial account of learning provides an alternative to these free-floating narratives about student literacy. From this perspective, ’literacy’ is an achievement that involves the successful coordination of human and non-human actors - including teachers, other learners, pupils, devices, texts and so on. Drawing on work undertaken as part of a JISC-funded project, we will present a critique of mainstream ’learner-centred’ accounts of digital literacy; outline the theoretical framework on which our work has been based; and present a series of case studies that show how an individual’s ability to act in a digitally literate way depends on much more than an assumed set of stable, internalised qualities. These cases involve data collected by students through multimodal journalling over a period of 9-12 months, and from in-depth interviews that explored what these meant to them. This analysis shows that learners’ practices are shaped in important ways by the social and material environments in which they are enacted, and that learners are engaged in an ongoing, improvisatory process of both adapting to the environments in which they work, whilst also adapting these environments.